Application of McGregors's XY leadership theory in education management: investigation of the link between preferred leadership style, intrinsic motivation and turnover intention. (30th July 2021) - Stefanovska-Petkovska, Miodraga; Bojadjiev, Marjan I.; Blazevski, Petar
The relationship between leadership style and intrinsic motivation was investigated, with the potential mediating effect of socio-demographic characteristics of respondents. The sample was consisted of 100 high school teachers from various high-schools on the territory of the city of Skopje, who completed a quantitative questionnaire. The research findings suggested that XY leadership is related to turnover intention, while intrinsic motivation is related to the socio-demographic characteristics of the teachers. Furthermore, intrinsic motivation fully mediated the relationship of job satisfaction with turnover intention and partially mediated the relationships of trust in organisation with turnover intention. The results suggested that the motivation of teachers to work can be targeted through adapting leadership styles and certain organisational characteristics and benefits provided to the employees.